The experiences of surrogate mothers: A qualitative study - Mahboubeh Taebi; Negin Masoudi Alavi; Seyed Mehdi Ahmadi (Kashan University of Medical Sciences, 2020)
Background: Surrogates are women who bear a genetically unrelated child for another individual or couple. Experiences of surrogate mothers need further investigation. Objective: The objective of the study was to answer the questions of what were the experiences of surrogate mothers and what problems they confronted during the process of surrogacy. Methods: The present study was a qualitative content analysis. Purposive sampling was used in the study. Pregnant women with various ages and educational levels were invited for semi-structured interviews. Graneheim and Lundman's method was used for analyzing the data. Results: In this study, 15 participants were interviewed. The codes extracted from the interviews were categorized into five main themes and 13 subthemes. The main themes were: (1) desperation; (2) pain and suffering with the subthemes of physical pain, emotional suffering, suffering caused by others, and fears; (3) emotional involvement and self-alienation; (4) looking for the positive aspects of the surrogacy with subthemes of positive interpretation of the experience, and the sense of pride; (5) and supportive systems including the commissioning parents, the surrogate's family, the health system, and the community as subthemes. Financial motivations were the reason for surrogacy which made women endure many physical, psychological, and social problems. The women expressed some positive feelings about surrogacy and also mentioned several support sources. Conclusion: Surrogate mothers reported numerous physical, emotional, and social problems that require better counseling services. A supportive system, especially the health system, should provide better and more humanistic services for surrogate mothers.